Research in organizational change and development. Volume 18 - Pasmore, William A.; Woodman, Richard W.; Shani, Abraham B. (Emerald, 2010)
Volume Eighteen of Research in Organizational Change and Development contains nine papers that address cutting edge challenges in organizational change, report the results of change-related research, and advocate methodological advances in the field. Papers by noted international authors such as Ed Lawler & Chris Worley, Hillary Bradbury, Benyamin Lichtenstein, John Carrol & Peter Senge, Rob Sloyan & Jim Ludema, and David Coghlan make for fascinating reading and set an ambitious agenda for future scholarship.
Keywords: Organizational change.; elektronické knihy; electronic books